O Ano da Morte de Ricardo Reis: a literatura como uma possibilidade de olhar para o passado. - Oliveira, Raíza Brustolin de (2016)
Considering that the literature has an impact on society and is influenced by it, this research has the general objective to analyze how literature presents itself as an opportunity for historic resumed. This are intertwined other goals as: Understanding the relation between literature and history; as it is a novel of historical nature, and mainly historiographical metafiction; and as the historical aspect is addressed in Saramago´s work The Year of the Death of Ricardo Reis. Thus, taking into consideration that the object contained two kinds of knowledge, literary and historical, research shows interdisciplinarity as research methodology. Thus, with regard to methodology, this research includes a qualitative and interdisciplinary literature. In this sense, the work begins with the presentation of the concept of grounded interdisciplinary mainly Pombo (2008) and Casanova (2006). Then discusses the relationship between literature and history showing that both are close and the first, and the second, also presents a perspective on the past, this reflection will be based on the approaches of Lenhardt and Pesavento (1998) and Hayden White (1994). Then, in the second chapter we study the historical nature of novels from Lukacs's approach (2011) and historiographical metafiction Linda Hutcheon (1991). This route provides a better analysis of the work The Year of the Death of Ricardo Reis, written by José Saramago, in the third chapter, which is historiographical metafiction, proposes a historical and critical perspective of the 1936 European in order to illustrate how the literature looks to the past. In this analysis of the historicity of the work, it is observed mainly three elements: the omniscient narrator intrusive, the character Ricardo Reis - fruit of intertextuality with Fernando Pessoa - and intertextuality with the news from newspapers of the time. Thus, it seeks to make clear that the literature as well as history, can contribute to the vision that one has of the past.